Quality Education Management In Madrasah - Setyowati, Ratna Dewi; Tisnawati, Nina; Pahrudin, Agus (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
The management of education in Islamic schools (madrasah) has become crucial in today's era, where the challenges of globalization and intense competition demand educational institutions that produce competent and high-quality graduates. This article aims to analyze the management of quality education in madrasahs, including legal foundations, principles, scope, issues, and applicable solutions. Using a literature review method, this article explains the concept of education management in madrasahs, such as the importance of visionary leadership, the development of teacher professionalism, the implementation of relevant curriculum, and continuous evaluation. The article also elaborates on the legal foundations governing education management in madrasahs, along with their basic principles. The scope of education management in madrasahs includes planning, organization, curriculum development, resource management, and evaluation. However, the article also identifies several challenges faced, such as resource constraints, irrelevant curricula, and low-quality learning. To address these challenges, the article offers quality-based solutions, such as drafting quality improvement plans, enhancing teacher quality, developing relevant curricula, utilizing educational technology, conducting continuous evaluations, and actively engaging the community. In conclusion, quality education management in madrasahs requires a comprehensive and sustainable approach, as well as the involvement of all relevant parties to create a conducive educational environment.